Folkloristični portreti iz treh stoletij Od baroka do moderne - Stanonik, Marija (ZRC SAZU, Založba ZRC, 2012)
This book ('Folkloristic Portraits from three Centuries. From baroque to modernism') preseints 18 profiled personalities from the Slovenian spiritual, cultural history and linguistics from 17th Century (J. V. Valvasor, J. Svetokriški, and 18th Century (M. Pohlin, U. Jarnik) up to most of them in the 19th Century (P. Danjko, A. M. Slomšek, M. Ravnikar-Poženčan, A. Murko, S. Vraz, E. Korytko, J. Trdina, M. Valjavec. V. Urbas, G. Krek, S. Škrabec, G. Križnik, S. Rutar) to K. Štrekelj. The personalities are illuminated from folkloristic view, following the prehistory this profession.